Is the G20 breaking up? - Rana, Pradumna Bickram (2022)
In the face of rising nationalism and populism worldwide, the G20 has failed to craft coordinated global responses to the COVID-19 pandemic. There is the possibility that the G20 may break up into the “G7 and the Rest” with each focusing on its own agenda.